RESPON PERTUMBUHAN BIBIT KAYU KUKU (Pericopsis mooniana (Thw.) Thw) TERHADAP INOKULASI FUNGI MIKORIZA ARBUSKULA LOKAL - Husna Husna (Jurnal Pemuliaan Tanaman Hutan, 2015)
Effectiveness of indigenous arbuscular mycorrhizal fungi (AMF) and the dependence of legumes to AMF application are determined by the compatibility of AMF and the host plant. This study aims to assess the effectiveness of indigenous AMF on growth, biomass and nutrient uptake of 5 months seedling of kayu kuku (Pericopsis mooniana (Thw.) Thw) grown in greenhouse. The six tested indigenous AMF were isolated from four rhizospheres of kayu kuku at Kolaka District: FMA-HA (natural forests Tanggetada, FMA-BJ (Bali Jaya village plantations), FMA-CA (Lamedai Nature Reserve, FMA-Vale (PT. Vale Indonesia Tbk.), and other two rhizospheres from Kendari city: FMAUHO (park area of Halu Oleo University), FMA-KG (urban forest in Southeast Sulawesi Governor's office). As comparison, there were also included a control (without AMF), a mycofer and an isolate from Kendari (kdr03). The study was designed in a randomized block design with 9 treatments and five replications. The results of study showed that in general AMF inoculations could increase the growth and nutrient uptake of the kayu kuku seedling. FMA-KG and FMA-UHO increased height, stem diameter, number of leaves, and root nodules. They also increased total dry weight at 260% and 281% above the control. In addition, FMA-KG increased total chlorophyll and nutrient accumulation. Levels of C organic and total N were not significantly affected by AMF treatment. Levels of total P, K, Ca and Mg of kayu kuku seedling were generally higher in control, but nutrient accumulation was higher in AMF treatment. There was a strong and significant correlation between nutrient accumulation and kayu kuku seedling biomass.